The application of the customized SERVQUAL model for career guidance training: Industry 4.0 challenges - Kononiuk, Anna; Gudanowska, Alicja E. (Journal of Business Economics and Management, 2022)
The importance of vocational guidance is growing, and the focus on modern tools enabling the development of competences such as flexibility, the ability to identify trends shaping the labour market and considering different scenarios of its development seem to be indispensable to survive in the world of work. The goal of the paper is to demonstrate a methodology and the outcomes of a research focused on the difference between the ideal characteristics and impressions of completed education by career counsellors in Poland. The research methods used are: the literature review, bibliometric analysis and the analysis and logical construction method. To diagnose the educational offerings the authors applied a modified SERVQUAL model. The observed gaps demonstrate the presence of significant discrepancies between the evaluation of the completed courses and the expectations of the respondents. Therefore, the expectations of those who took part in the survey about the quality of education in the field of vocational guidance are not fulfilled. The results of the analysis allow also to conclude that curricula only take little account of trend and scenario analysis tools specific to Industry 4.0; and this demonstrates a major challenge for including this curriculum content in the area of vocational guidance. First published online 01 April 2022